A perspectiva dos ângulos: os espaços culturais nos contos de Aurélio Buarque de Holanda e Breno Accioly - Araújo, Elton Jônathas Gomes de (2025)
The primary objective of this thesis is to conduct a comparative analysis of the works of short story writers Aurélio Buarque de Holanda and Breno Accioly, highlighting recurring themes, representations of space, and the sociocultural relationships depicted in their fiction. Through this study, it aims to explore how these authors, although situated within the same literary context of the 1930s and 1940s, developed narratives with thematic particularities that reflect both common and divergent elements. To achieve this, the work is structured into five parts. In the first part, the literary landscape of the period is contextualized, providing a framework for understanding the cultural aspects that influenced both authors. In the second part, the essential characteristics of the short story are explored, drawing on the theoretical perspectives of authors such as Poe (1985), Cortázar (2006), and Piglia (2004). In the following two chapters, the biobibliographical trajectories of Aurélio Buarque de Holanda and Breno Accioly are analyzed, emphasizing their literary and critical productions, as well as their participation in the cultural milieu of the time. In doing so, it highlights some editorial paratexts from the perspective of Genette (2018) and presents peritexts that contribute to the understanding of their works and their context. Additionally, it examines certain aspects that interact with their short stories. In the fifth chapter, a direct comparison of their works is deepened, identifying convergent themes—such as the exploration of childhood, power, violence, death, and solitude—and those that distinguish them, with a particular focus on the representation of cultural spaces. For this purpose, authors such as Blanchot (2011), Eagleton (2011), Brayner (1979), Bosi (2022), Sontag (2003), and Nunes (2013) provide robustness to the proposed discussions. Thus, this study aims to offer an in-depth analysis of the works of Aurélio Buarque de Holanda and Breno Accioly, as well as to establish a substantial comparison of the dialogue present in their narratives. By elucidating the thematic, spatial, and sociocultural peculiarities of these short story writers, it intends for this research to contribute to a greater understanding of 20th-century Brazilian literature, particularly regarding these two currently overlooked fiction writers.